Los fosfatos del Sahara Occidental y los principales productores mundiales de roca fosfática: política versus estrategia empresarial, 1969-1975 - Martínez Milán, Jesús María (El Colegio de México, 2019)
Between the end of the 1960s and the beginning of the 1970s, the world’s phosphate market went through a period characterized by a fall in demand and a price war between the major producers. At that time, Saharan phosphate burst onto the world market. In this paper, I intend to analyze the strategies used by the major producers to control Saharan phosphate. I argue that Spain allied with Morocco in order to share the market with its biggest competitor. However, this strategy began to fail as soon as Madrid prioritized the interests of the Spanish fertilizer industry over those of Fosfatos de Bu Craa, S.A. (Fosbucraa). All this took place at the beginning of a new era marked by the withdrawal of Spain from Sahara and a fall in the international price of phosphate.